Relationship between postpartum mothers' knowledge about psychological adaptation during the postpartum period (taking in, taking hold dan letting go) and postpartum stress - Kasmara, Dwi Pratiwi; Anita, Yola fitri (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2023)
Stress within certain limits can have a positive impact and motivate us to achieve a goal. If stress is left unchecked it can build up. There are three stages of psychological adaptation during the postpartum period, namely taking in, taking hold and letting go. The purpose of this study was to determine the relationship between mother's knowledge (taking in, taking hold and letting go) with stress events in postpartum mothers. This study is an analytic study with a cross-sectional design. The sampling technique used in this study was non-probability sampling in the form of accidental sampling. The population is 265 postpartum mothers at the pepper plantation health center in Langkat district. Sampling technique with accidental sampling as many as 72 respondents. The bivariate test uses the chi square test. The results showed that the majority age of postpartum mothers was 21-35 years as many as 51 people (70.8%). The education of the majority of postpartum mothers is junior high school as many as 31 people (43.1%). The majority of postpartum mothers work as farmers with 43 people (59.7%). Knowledge of the majority of postpartum mothers is lacking as many as 45 people (62.5%). The incidence of stress on postpartum mothers was 49 people (68.1%). There is a relationship between postpartum mother's knowledge about Postpartum Psychological Adaptation (taking In, Taking Hold and letting Go) with stress events during the postpartum period.